A stable dual-emitting dye@LMOF luminescence probe for the rapid and visible detection of organophosphorous pesticides in aqueous media. Issue 6 (15th January 2020) - Zhang, Jie; Zhou, Wendi; Zhai, Lijun; Niu, Xiaoyan; Hu, Tuoping
Abstract : The composite RhB@LMOF 1 was synthesized and exhibited sensitive and selective recognition ability for the detection of organophosphorous (OPs) pesticides in aqueous media. Abstract : A novel 3D supermolecular metal–organic framework (LMOF 1 ) {[Cd1.5 (TCPB)(phen) 2DMF·3.5dioxane·H2 O]} n (H3 TCPB = 1, 3, 5-tris(4-carbonylphenyloxy)benzene and phen = 1, 10-phenanthroline monohydrate) was solvothermally synthesized, and after the incorporation of the fluorescent guest molecule rhodamine B (RhB) into the channel of LMOF 1, the composite RhB@LMOF 1 was successfully prepared. Because the channels of LMOF 1 could restrain the dissociation of the RhB aggregates, RhB@LMOF 1 displayed outstanding stability under varying treatment conditions. The solid-state fluorescence spectrum analysis showed that RhB@LMOF 1 possesses the characteristic emissions of both RhB and LMOF 1 . Subsequently, the luminescence sensing of RhB@LMOF 1 for six types of pesticides was investigated at room temperature. The results demonstrated that RhB@LMOF 1 could sensitively and selectively recognize organophosphorous (OP) pesticides, which is mainly attributed to the synthetic effect of the internal filter effect (IFE) and photo-induced electron transfer (PET).